The economics of casino taxation - Benar, Hasret; Jenkins, Glenn P. (My University, 2008)
In this article, a model of the costs of a casino is developed that focuses on the implications for economic welfare of different taxation schemes for casinos. The situation being considered is in a country where casinos cater exclusively to foreign tourists. The goal of the country is to determine the maximum amount of taxes that can be extracted from the activities of this sector under different systems of taxation. When the price of gambling is set by regulation above its competitive level, the economic losses created by excessive investment in the sector can be reduced by taxation. A turnover tax on the amount gambled can maximize both tax revenue and the economic welfare of the country. Due to administrative constraints, a number of countries rely on the taxation of the casinos' fixed assets or a combination of a turnover tax and a tax on fixed costs. The model is applied to the situation in North Cyprus. The annual economic efficiency loss from its poorly designed tax policies on casino gambling is estimated to be about 0.5% of GDP.
Keywords: cost; economic impact; gambling; modeling; tax system; Asia; Cyprus; Eurasia; Middle East; Northern Cyprus